Evaluation of California's Statewide Mental Health Prevention and Early Intervention Programs Summary of Key Year 2 Findings - Eberhart, Nicole K. (RAND Corporation, 2015)
This report summarizes key findings from the second year of an evaluation of the California Mental Health Services Authority's statewide prevention and early intervention programs.